Microaggressive incidents towards women in the healthcare context: A qualitative and intersectional perspective - Piccinelli, Elena (2019)
Microaggressions are subtle forms of discrimination, expressed in slights, insults, invalidations and indignities directed to minority, marginalized and discriminated groups. Microaggressions are often unconsciously perpetrated, socially normalized and naturalized. The present qualitative study aimed to analyze and understand the microaggressive incidents experienced by women with different intersectional identities (White women, women of Color, immigrant women, straight women, LGBTQ+ women, functionally diverse women) in the Portuguese healthcare context. Semi-structured interviews, centered around the Critical Incident Technique, were conducted. Seventeen women that self-identified as feminists, activists and/or that were engaged with NGOs and organizations actively committed to social causes, participated in the study. Content and thematic techniques for qualitative analysis were used in order to recognize the different microaggressive forms (microinsults, microinvalidations, microinvalidations), levels of manifestation (verbal, nonverbal/behavioral, environmental) and themes perpetrated in the healthcare context. At the end of the study, and based on the information collected, brief vignettes showcasing critical incidents were created with the potential of being implemented in diversity training programmes.